Peningkatan Produktivitas Guru Dalam Mengelola Kelas Melalui Supervisi Klinis Pengawas Sekolah - Nonok Mulyati (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to determine whether there is an increase in teacher productivity in the learning process after the implementation of Clinical Supervision of School Supervisors at SMP Negeri 1 Warunggunung. This research uses action research in two rounds (cycle). Each round consists of four stages, namely: design, action, observation and reflection. The results of this study indicate that there is an increase in teacher discipline in the learning process through Clinical Supervision of School Supervisors carried out by school supervisors for teachers at SMP Negeri 1 Warunggunung. This increase in productivity can be seen based on the data obtained in each cycle. For the results of the assessment in the first cycle, the level of achievement was 61.96%, an increase of 22.06% to 84.02% in the second cycle. For the performance category in the first cycle of 46 teachers, 7 people are in the poor category with a percentage of 15.22%, 37 people are in the moderate category with a percentage of 80.43%, and only 2 people are in a good category with a percentage of 4.35%. In the second cycle, there was a significant change because there were no teachers in the less or 0% category, there were still 6 teachers who were in the sufficient category with a percentage of 13.04% and 40 teachers in the good category with a percentage of 86.96%.